Clinical and neurological disorders in children against the background of a previous herpesvirus infection - Shuhrat Niyazov; Aziza Djurabekova; Gulandon Khakimova (International Journal of Human Computing Studies, 2020)
Despite a significant amount of research on herpesvirus lesions of the nervous system in children , questions regarding the diagnosis of the spectrum of forms of the disease , the fight against the consequences of the disease , many points remain open . The paper presents cases of demage to the central and peripheral nervous system by the herpes simplex virus in children , features of the course , clinical and neurological forms , the prognosis of the disease depending on the severity.